Proceedings of the 2012 International Conference on Quantitative InfraRed Thermography 2012
DOI: 10.21611/qirt.2012.270
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact multi-spectral imaging combined with thermography to determine physiological changes in perfusion during clinical interventions

Abstract: Reflectance spectroscopy and thermography are used as non-invasive, non-contact imaging method to study the physiology of skin processes or pathophysiology of skin diseases. In this proceeding the development of a multispectral imaging system based on a tunable LED light source is described. The system is validated under laboratory conditions on volunteers. Different algorithms to calculate the O2Hb and HHb changes in the tissue are being developed and the results are presented for different sets of selected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Another important step is to translate these findings to in vivo studies on tissues. Other tissue characteristics such as tissue perfusion, which is important for healing and can be detected using MSI, 34 should also be included in the analysis and suture location optimization. Such suture maps processed in real time may potentially provide access to the best tissue information for anastomosis and thus mitigate the highly variable experiences and intraoperative decisions of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Another important step is to translate these findings to in vivo studies on tissues. Other tissue characteristics such as tissue perfusion, which is important for healing and can be detected using MSI, 34 should also be included in the analysis and suture location optimization. Such suture maps processed in real time may potentially provide access to the best tissue information for anastomosis and thus mitigate the highly variable experiences and intraoperative decisions of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Recently, several research groups have made great progress in utilizing LEDs as illuminating light sources in imaging tissue hemoglobin concentrations and oxygenation changes for skin cancer. [20][21][22] These studies indicated that NIR LEDs have the ability to characterize the optical properties of superficial lesions. In 2005, Chance et al developed a hand-held probe with a three-wavelength LED for a CW NIR spectrometer.…”
Section: Introductionmentioning
confidence: 95%